The People’s University of the Air:: St. Francis Xavier University Extension, Social Christianity, and the Creation of CJFX - McGowan, Mark (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2012)
Broadcast historians have identified government regulations restricting the ownership of broadcast licenses and programming by religious groups as having successfully limited the influence of religion on the public airwaves in Canada. Evidence for such claims has been derived primarily from the examination of the archives of the CBC and not from private broadcasters, who were far more numerous in Canada. In Antigonish, Nova Scotia, the priest-professors at St. Francis Xavier University established a private radio station, CJFX, which effectively allowed them to propagate the principles of Catholic social teaching to large listenership (suggesting that religious groups were quite creative in their use of media).